PENGARUH DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PABRIK KELAPA SAWIT (PKS) PT. PERKEBUNAN NUSANTARA V SEI ROKAN KEC. PAGARAN TAPAH DARUSSALAM KAB. ROKAN HULU - Fitri Afriyani Christian; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to determine the effect of labor discipline on employee productivity Palm Oil Factory production section (PKS) PT. PTPN V Sei Rokan district. Pagaran Tapah Darussalam Kab. Rokan Hulu. Labor discipline as an independent variable (X) and employee productivity as the dependent variable (Y). This research was conducted to the production employees as many as 63 people.Data were obtained from questionnaires and subsequently processed to then be tested using statistical analysis as a simple linear regression analysis, t-test, correlation analysis and determination using SPSS. The results showed that the results of hypothesis testing t test. thitung (14.241)> t table (2,000). This suggests that the labor discipline effect on employee productivity, the influence of labor discipline on employee productivity Palm Oil Factory production section (PKS) PT. PTPN V Sei Rokan district. Pagaran Tapah Darussalam Kab. Rokan Hulu amounted to 76.9% while the remaining 23.1% is influenced by other factors.Keywords: work discipline, labor productivity